Ethical Leadership in HRM: A Critical Analysis of the Role of HRM Practices in Promoting Ethical Behavior and Corporate Social Responsibility - Saudin, La (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This study explores the contextual factors that influence the relationship between Human Resources (HRM) ethical leadership, employee ethical behavior, and corporate social responsibility (CSR). Through a literature review, we examine the influence of organizational culture, company values, government regulations, pressure from stakeholders, and the role of industry and business environment in shaping the dynamics between these variables. Findings show that alignment between HRM practices and organizational culture, CSR authenticity, and government regulations play a key role in shaping employee behavior, organizational commitment, and company performance. In addition, industry characteristics and business environment moderate the relationship between these variables. These results emphasize the importance of understanding the complexity of the relationship between HRM ethical leadership, employee ethical behavior, and CSR in various organizational contexts.